APPLICATION OF MEDICAL IMAGING COMPUTED RADIOGRAPHY (CR) SYSTEM IN INDUSTRIAL IMAGING: LEAD ACID BATTERY INSPECTION - Abdul Majid, Zafri Azran (International Journal of Allied Health Sciences, 2018)
Introduction: Non destructive testing (NDT) is a procedure to assess the internal components without disassembling the outer components. Industrial imaging uses high energy x-rays to penetrate materials while x-rays used in medical imaging has exposure limitation. The purpose of this paper is to determine the optimum technical factors (kVp, mAs, and SID) used in medical imaging Computed Radiography (CR) system suitable for industrial imaging application to inspect lead acid battery. Methods: Lead acid battery is exposed to radiation with predetermined technical factors utilized in medical imaging. The kVp, mAs, and SID are varied throughout the experiment. The optimum technical factors obtained are further used to expose the battery at six different angles for inspection of lead plates. The sizes of lead plates are measured using imageJ software and the measured length is compared to the actual sizes of lead plates. Results: At 15 mAs, two values with the smallest difference to the original size of the lead plates are produced which is at 75 kVp and 125 kVp. Based on the technical factors used in this experiment, it is concluded that 15 mAs is the optimal mAs that can be used to provide the measurement with the least difference when compared to the original size of the lead plates. All measurement with the smallest difference when compared to the original sizes of lead plates are obtained at 125 kVp which is 4.19 cm (plate C when mAs at 5), 4.23 cm (plate C when mAs at 10), and 4.23 cm (plate C when mAs at 15). This indicates that 125 kVp is suitable to be used for inspection. The accurate measurement of lead plates is achieved when 100 cm SID is used. When exposed, white lead sulphate is seen coating the lead plates. Conclusion: X-rays used in medical imaging can be applied in industrial imaging for lead acid battery inspection as it also possess high energy and penetrating power.